2009
DOI: 10.1111/j.1365-2052.2008.01822.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of single nucleotide polymorphisms in the endothelial differentiation sphingolipid G‐protein‐coupled receptor 1 gene with marbling in Japanese Black beef cattle

Abstract: Marbling defined by the amount and distribution of intramuscular fat, so-called Shimofuri, is an economically important trait of beef cattle in Japan. The endothelial differentiation sphingolipid G-protein-coupled receptor 1 (EDG1) gene, involved in blood vessel formation, has been previously shown to be expressed at different levels in musculus longissimus muscle between low-marbled and high-marbled steer groups. It is located within the genomic region of a quantitative trait locus for marbling, and thus was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 18 publications
5
49
1
Order By: Relevance
“…Eighteen substitutions were found in the 5ʹUTR region (g.3312T>C, g.3360T>G, g.3398G>A, g.3513G>A, g.3520T>C, g.3623C>T, g.3665C>G, g.3807A>G, g.3980C>A, g.3986A>T, g.3989C>A, g.3092C>T, g.4207A>G, g.4210T>G, g.4274T>A, g.4396T>C, g.4462G>A, and g.4586A>T) while only six were observed in the 3ʹUTR region (g.40G>A, g.68A>C, g.79T>C, g. 150G>T, g.1979A>T, and g.2033G>A). Nucleotide substitutions in these regions of S1PR1 were previously suggested to be associated with the level of marbling in meat of Japanese Black beef cattle (Yamada et al, 2009a;2009b). Eight synonymous substitutions were also found in the coding region (g.2280C>T, g.2295T>C, g.2508C>G, g.2682T>C, g.2856T>G, g.2913A>G, g.3015T>C, and g.3102T>C).…”
Section: Discussionmentioning
confidence: 87%
“…Eighteen substitutions were found in the 5ʹUTR region (g.3312T>C, g.3360T>G, g.3398G>A, g.3513G>A, g.3520T>C, g.3623C>T, g.3665C>G, g.3807A>G, g.3980C>A, g.3986A>T, g.3989C>A, g.3092C>T, g.4207A>G, g.4210T>G, g.4274T>A, g.4396T>C, g.4462G>A, and g.4586A>T) while only six were observed in the 3ʹUTR region (g.40G>A, g.68A>C, g.79T>C, g. 150G>T, g.1979A>T, and g.2033G>A). Nucleotide substitutions in these regions of S1PR1 were previously suggested to be associated with the level of marbling in meat of Japanese Black beef cattle (Yamada et al, 2009a;2009b). Eight synonymous substitutions were also found in the coding region (g.2280C>T, g.2295T>C, g.2508C>G, g.2682T>C, g.2856T>G, g.2913A>G, g.3015T>C, and g.3102T>C).…”
Section: Discussionmentioning
confidence: 87%
“…However, this EDG1 SNP marker did not affect other traits such as live weight, carcass weight, dressing percentage, backfat thickness, and M. Longissimus dorsi area. Yamada et al (2009a) first identified two SNPs in the 5'-UTR and the 3'-UTR of EDG1 gene, referred to as c.-312A>G and c.*446G>A, respectively, and analysed association of the SNPs with marbling and subcutaneous fat thickness in Japanese Black beef cattle. The g.166A>G SNP identified in this study is identical to previously reported SNP (c.-312A>G) in Japanese Black cattle.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, eating quality traits such as taste, juiciness and tenderness of meat are influenced by the amount of intramuscular fat (Platter et al, 2005;Chung et al, 2008). High levels of marbling improve the palatability and acceptability of beef by affecting the taste and tenderness of the meat (Busboom et al, 1993;Boylston et al, 1995;Matsuishi et al, 2001;Yamada et al, 2009a). In addition, marbling is the most economically important meat quality trait in beef industry of Korea because carcass value is primarily determined by the degree of marbling.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cardoso et al (2014), Hoashi et al (2007), and Yamada et al (2009) have reported the effects of genetic polymorphism of particular genes on the productivity of beef cattle. Furthermore, Nishimaki et al (2016), Kaneda et al (2011), and Okuda et al (2017) have reported the frequency and distribution of genotypes in cattle breeds to investigate their genetic potential.…”
mentioning
confidence: 99%
“…SCD and SREBP1 genes are associated with fatty acid composition (Taniguchi et al 2004;Hoashi et al 2007), EDG1, DGAT1, and NCAPG, and MC1R genes are associated with beef marbling (Yamada et al 2009), milk composition (Grisart et al 2002), carcass weight (Eberlein et al 2009), and coat color determination (Klungland et al 1995), respectively. We also investigated mitochondrial (zebu, indicine) type haplogroups (Achilli et al 2009;Verkaar et al 2003), investigation of the distribution of the mtDNA and Y-chromosome haplotypes will be informative for genetic characterization of Pesisir cattle.…”
mentioning
confidence: 99%